Expression of B7 (CD80) and CD40 antigens and the CD40 ligand in Hodgkin's disease is independent of latent Epstein—Barr virus infection. Issue 2 (April 1995) - Murray, P G; Oates, J; Reynolds, G M; Crocker, J; Young, L S
Abstract : Aim —To examine the expression of CD40 and B7 (CD80) antigens and the CD40 ligand in Hodgkin's disease. Methods —Antigen and ligand expression was studied in 17 cases of Hodgkin's disease using immunohistochemistry. The study included 11 cases of Hodgkin's disease in which latent Epstein-Barr virus (EBV) infection could be demonstrated within tumour cells by in situ hybridisation for the EBV encoded early RNAs (EBERs). Results —In all cases, irrespective of EBV status, Reed-Sternberg cells and their variants (HRS cells) showed strong expression of both B7 and CD40 antigens. CD40 ligand expression was not shown in HRS cells but was confined to a subset of small lymphocytes some of which were seen to be in intimate contact with HRS cells. Paraffin wax sections from a further 60 cases of Hodgkin's disease were examined for CD40 and EBER expression alone. The CD40 antigen was identified in HRS cells in all of these cases irrespective of EBER expression. Conclusions —As CD40 and B7 expression are features of professional antigen presenting cells, these results provide further evidence that HRS cells may have antigen presenting properties and that this may contribute to the characteristic recruitment and activation of non-malignant lymphocytes which is a feature of Hodgkin's disease. The ability of HRS cells to activate Th cells may in turn contribute to their own survival through the induction of the gp39/CD40 pathway.